Vogt – Koyanagi Harada Syndrome in a Pakistani Female: Doi:10.36351/pjo.v36i4.1120 - Rebecca, Dr; Junejo, Murtaza Sameen; Shaikh, Fahad Feroz; Laghari, Nazir Ashraf (Pakistan Journal of Ophthalmology, 2020)
Vogt-Koyanagi-Harada syndrome is a rare multiorgan inflammatory disorder characterized by bilateral uveitis with serous retinal detachment and is often associated headache, hearing loss, vitiligo, and poliosis. Here we present a case of 37 years old female who presented with chronic photophobia, redness and progressive decreased vision in both eyes for 5 years along with cutaneous and hearing symptoms. On Ocular examination her best-corrected visual acuity was 6/60 OD and perception of light OS, while the intraocular pressure was 16 mm?Hg OD and 18?mm?Hg OS, measured with Goldmann applanation tonometer. The slit-lamp examination of right anterior segment showed diffuse Keratic precipitates along with diffuse iris atrophy and seclusion pupillae (360 degree). On detailed examination she found to be a case of VKH syndrome. This case is presentedto familiarize ophthalmologists and health care professionals about its findings and complications that are usually found in such patients. Key Words: Uveitis, Poliosis, Vogt Koyanagi Harada, vitiligo.